Why Google Stores Billions of Lines of Code in a Single Repository. - POTVIN, RACHEL; LEVENBERG, JOSH (Communications of the ACM, 2016)
The article discusses the storage of the codebase of the search engine firm Google Inc. in a monolithic source repository. Topics include the use of the Piper workflow and the access system Clients in the Cloud (CitC), the prevention of unnecessary dependencies in the repository's code, and a comparison of Google's repository to distributed version control systems (DVCSs) such as Git.